(untitled) (Altre Modernità, 2019)
Because of its very nature, the tourism experience involves contact with different contexts and cultures, which, once the destination has been reached, may pose cultural and communicative problems because the tourist has to rely on what can be found in situ. In this context, the quantity, and especially the quality, of the information offered can influence the tourist’s enjoyment of the whole experience. This calls for the presence, at an attraction site, of translations of informative texts, whose quality is regarded as an indication of the attention and care taken by the destination for the satisfaction of visitors’ needs. Drawing on relevant scholars (Duran Muñoz; Sumberg; Cappelli “Translation”; Tognini and Manca) working in this context, this paper will investigate how texts provided as panels for visitors have been translated from Italian into English. Attention will be paid to panels found in a few Italian churches (in Milan), since, to the best of our knowledge, little if any research has been done on this topic. The focus of this investigation will be on the main linguistic features characterizing Italian texts and their English translations found on panels, including an analysis of lexical and syntactic elements employed by the authors to express the informative content of texts. Possible mistakes and inaccuracies in the translating process will be presented and explanations will be provided concerning how target language rules and conventions have been violated during the translation process. In addition, a series of possible solutions to improve the quality of this kind of specialized translation will be proposed, in order to suggest best practices.